Vergence/accommodative therapy for symptomatic convergence insufficiency in children: Time course of improvements in convergence function. (22nd October 2022) - Jenewein, Erin C.; Cotter, Susan; Roberts, Tawna; Kulp, Marjean; Mitchell, G. Lynn; Jones‐Jordan, Lisa A.; Chen, Angela M.; Hopkins, Kristine; Huang, Kristine; Amster, Deborah; Fecho, Gregory; Tyler, Julie; et al.
Abstract: Purpose: To evaluate the time course of improvements in clinical convergence measures for children with symptomatic convergence insufficiency treated with office‐based vergence/accommodative therapy. Methods: We evaluated convergence measures from 205, 9‐ to 14‐year‐old children with symptomatic convergence insufficiency randomised to office‐based vergence/accommodative therapy in the Convergence Insufficiency Treatment Trial – Attention and Reading Trial (CITT‐ART). Near‐point of convergence (NPC) and near‐positive fusional vergence (PFV) were measured at baseline and after 4, 8, 12 and 16 weeks of therapy; mean change in NPC and PFV between these time points were compared using repeated measures analysis of variance. Rates of change in NPC and PFV from: (1) baseline to 4 weeks and (2) 4–16 weeks were calculated. For each time point, the proportion of participants to first meet the normal criterion for NPC (<6 cm), PFV blur (break if no blur; >15Δ and >2 times the exodeviation) and convergence composite (NPC and PFV both normal) were calculated. Results: The greatest change in NPC and PFV (7.6 cm and 12.7 Δ) and the fastest rate of improvement in NPC and PFV (1.9 cm/week and 3.2 Δ/week, respectively) were both found during the first 4 weeks of therapy, with both slowing over the subsequent 12 weeks. After 12 weeks of therapy, the NPC, PFV and convergence composite were normal in 93.2%, 91.7% and 87.8% of participants, respectively, and normalised with another 4 weeks of therapy in 4.4%, 2.0% and 4.4% of participants, respectively. Conclusion: Although the greatest improvements in NPC and PFV occurred in the first 4 weeks of therapy, most participants had weekly improvements over the subsequent 12 weeks of treatment. While most children with convergence insufficiency obtained normal convergence following 12 weeks of therapy, an additional 4 weeks of vergence/accommodative therapy may be beneficial for some participants.